Guns vs. Canes: The Fiscal Implications of an Aging Population - Torrey, Barbara Boyle (American Economic Review, 1982)
The share of the federal budget devoted to the older population (defined in this paper as people who are 65 and above) has expanded substantially from approximately 2 percent in 1940 to 25 percent today. Over the next fifty years this older population is expected to more than double in size and increase from 11 percent of the population to between 20 and 26 percent. These increases will come in two distinct periods, the 1980's and the twenty years beginning in 2010. Even if no further responsibilities are assumed by the federal government, this population increase alone will put inexorable fiscal pressure on future federal budgets.